ANALISIS DETERMINAN YANG MEMENGARUHI PENERIMAAN OPINI AUDIT GOING CONCERN - Ristina Clarisa (2022)
This research is a quantitative study with the aim of knowing and analyzing the factors that influence the acceptance of going concern audit opinion. The factors studied in this case are debt default, opinion shopping, company size, and company growth. The population in this study are transportation logistics companies and property real estate companies listed on the Indonesia Stock Exchange in 2018-2020. The data samples was determined using purposive sampling method and obtained a 222 samples from 74 companies. Hypothesis testing using logistic regression analysis with SPSS version 26 program. Result of this study indicate that opinion shopping has a significant positif effect on the acceptance of going concern audit opinion, company growth has a significant negative effect on the acceptance of going concern audit opinion, meanwhile debt default and company size has no significant effect on the acceptance of going concern audit opinion.